The politics of aid and poverty reduction in Africa: A conceptual proposal and the case of Mali - Isaline Bergamaschi (University of Duisburg-Essen, Käte Hamburger Kolleg / Centre for Global Cooperation Research (KHK/GCR21), 2016)
How can we conceptualise the politics of aid and account for the effects of internationally-driven poverty reduction policies in the Global South? This Working Paper offers a conceptual framework that goes beyond two common assumptions in the academic literature and the activist milieux: on the one hand, the idea that one-size-fits-all international recommendations and PRSPs are imposed on recipient governments; on the other hand, the idea promoted by the World Bank and shared by most donors that Poverty Reduction Strategy Papers (PRSPs) are efficient when “owned” by the recipient government. To do so, the Working Paper takes the case of Mali in the 2000s and presents the uses and trajectories of PRSPs in this West African country. The Working Paper distances itself from the two notions of imposition and “ownership” and takes recipient agency seriously. To investigate the politics of aid and poverty reduction in aid-dependent countries, it offers an analytical framework which borrows from the notion of “appropriation”. It argues that the PRSPs in Mali have been successfully appropriated by public actors, i.e. political leaders, public servants and civil society representatives. This Working Paper shows how, over one decade, the PRSP has shifted from being a “World Bank thing”, i.e. a mere conditionality to comply with, to being treated by public actors as the “reference framework”. This has happened through modalities and processes of appropriation which differed from the scenario initially envisaged by the World Bank but have ensured that the PRSP has become truly Malian, i.e. embedded in the country's socio-political fabric.
urn:nbn:de:hbz:464-20160912-102716-1
Keywords: 320; Politics of aid; aid dependency; poverty reduction; ownership; appropriation; crisis; Mali; international political economy; development studies; development anthropology; public policy and policy tools